Developmentalism: An Obscure but Pervasive Restriction - J. E. Stone (Arizona State University, 1996)
Despite continuing criticism of public education, experimentally demonstrated and field tested teaching methods have been ignored, rejected, and abandoned. Instead of a stable consensus regarding best teaching practices, there seems only an unending succession of innovations. A longstanding educational doctrine appears to underlie this anomalous state of affairs. Termed developmentalism, it presumes "natural" ontogenesis to be optimal and it requires experimentally demonstrated teaching practices to overcome a presumption that they interfere with an optimal developmental trajectory. It also discourages teachers and parents from asserting themselves with children. Instead of effective interventions, it seeks the preservation of a postulated natural perfection. Developmentalism's rich history is expressed in a literature extending over 400 years. Its notable exponents include Jean Jacques Rousseau, John Dewey, and Jean Piaget; and its most recent expressions include "developmentally appropriate practice" and "constructivism." In the years during which it gained ascendance, developmentalism served as a basis for rejecting harsh and inhumane teaching methods. Today it impedes efforts to hold schools accountable for student academic achievement.